Pengaruh Kartu Kredit, Dana Float dan Suku Bunga Kebijakan Terhadap Velocity Of Money Di Indonesia - Mustika Sasikarani; Thomas Andrian; Ukhti Ciptawaty (Goodwood Publishing, 2022)
Technology that is developing rapidly, one of which has provided changes to the payment system from cash to payment system non-cash. Changes in the form of payment instruments resulted in a decrease in the use of cash in the community which then had an impact on the velocity of money or the speed of money due to more liquid transactions and more efficient transactions. This study aims to determine the effect of credit cards, electronic money floating funds and interest rates on the velocity of money in Indonesia. This study uses data sourced from the official website of Bank of Indonesia and the Central Statistics Agency (BPS) of Indonesia. The research data used is in the form of monthly time series data from January 2017 to December 2021, the analytical tool used is the Error Correction Model (ECM). The results show that non-cash transactions in the form of credit cards and interest rate policies have a positive effect on money circulation in the long term, while electronic money floating funds have a negative effect on money circulation in Indonesia in the short and long term.